An acidic pH independent piperazine–TPE AIEgen as a unique bioprobe for lysosome tracing. Issue 11 (25th September 2017) - Cai, Yuanjing; Gui, Chen; Samedov, Kerim; Su, Huifang; Gu, Xinggui; Li, Shiwu; Luo, Wenwen; Sung, Herman H. Y.; Lam, Jacky W. Y.; Kwok, Ryan T. K.; Williams, Ian D.; Qin, Anjun; et al.
Abstract : PIP–TPE's fluorescence turns on blue due to the large viscosity of lysosomes which restricts intramolecular motions but it red-shifts in the bulk. Abstract : Lysosomes are involved in a multitude of cellular processes and their dysfunction is associated with various diseases. They are the most acidic organelles (pH 3.8–6.6, size 0.1–1.2 μm) with the highest viscosity (47–190 cP at 25 °C) in the cell. Because of their acidity, pH dependent non-AIE active fluorescent lysosomal probes have been developed that rely on protonation inhibited photoinduced electron transfer (PET). In this work, an acidic pH independent lysosome targetable piperazine–TPE (PIP–TPE) AIEgen has been designed with unique photophysical properties making it a suitable probe for quantifying viscosity. In a non-aggregated state PIP–TPE shows deep-blue emission as opposed to its yellowish-green emission in the bulk. It possesses high specificity for lysosomes with negligible cytotoxicity and good tracing ability due to its better photostability compared to LysoTracker Red. In contrast to most known lysosome probes that rely solely on PET, restriction of intramolecular motion (RIM) due to the larger viscosity inside the lysosomes is the mechanism responsible for PIP–TPE's fluorescence. PIP–TPE's high selectivity is attributed to its unique molecular design that features piperazine fragments providing a perfect balance between lipophilicity and polarity.